Government Bureaucratic Behavior in Optimizing Institutional Investment Licensing Services (Case Study in Garut Regency) - Widaningsih; Novianita Rulandari; Eliya Fatma (Yayasan Ilomata, 2023)
To improve the economic capability of a region, one of them is by investing in the Endogenous Development paradigm, the strategy is to harmonize natural forces with the strength of human resources. However, we still find many problems when we will make this investment, one of the problems is related to licensing which is still very complicated, requires a very long bureaucratic path, and buys complicated. This is what encourages researchers to research the problem of the still difficult licensing path. Researchers conducted this study using qualitative research methods which analyzed data from interviews through informants related to investment. The results obtained in this study show that there is still a high gap between investment interest and investment realization, which is one of the causes is still There are weaknesses in bureaucratic behavior in implementing policies on investment.